Well-being and well-becoming through the life-course in public health economics research and policy: A new infographic - Edwards, Rhiannon Tudor (Frontiers in Public Health, 2022)
Background The term “well-becoming” is not new, but is not routinely used in our everyday language or in research in public health economics. It has been applied in early years research. Well-becoming can be thought of as our multitude of life-journeys toward meaning and purposefulness. Objective To develop a new infographic in the spirit of the Dahlgren and Whitehead rainbow infographic of social determinants of health. The purpose being to redefine well-being as a process of growth through life, articulated as well-becoming. Methods A rapid review of life-course stage appropriate models of well-being was undertaken with stages of the life-course as defined as: preconception and birth; early years; adolescence; working, parenting and caring; older age, and death. Infographics in this area were identified and the information above was used to design a new infographic with the concept of well-being and well-becoming at its center. Results A new infographic reflecting an underlying concept of “the wheel of life” is presented. It shows movement through the life-course at its center, with concentric rings summarizing personal, local, and national and global factors that have an impact on well-being and well-becoming of individuals through the life-course. Of note, is the inclusion of death, which is a topic often avoided. Prepared during 2021–22, the infographic reflects the role of pandemic and war within the national and global ring of influential factors. I reflect on three ways in which health economists are currently using a life-course approach and the concept of well-becoming in the economic evaluation of individual programs and at a population level of government policy. Conclusion Moving from solely focusing on a concept of well-being to a concept of well-being and well-becoming acknowledges the influence that socioeconomic and other conditions in a particular life-course stage have on subsequent life-course stages, and the cost-effectiveness of intervening across the life-course.